INFLUENCE OF INHIBITORS OF TRANSCRIPTION FACTOR KAPPA B ON DEPOLIMERIZATION OF BIOPOLYMERS IN PERIODONTAL CONNECTIVE TISSUE UNDER SYSTEMIC INFLAMMATORY RESPONSE IN RATS - Yelinska, A.M.; Denisenko, S.V.; Liashenko, L.I.; Kostenko, V.O. (World of Medicine and Biology, 2020)
The article presents the results obtained in the experiment on 40 white rats aimed at investigating the influence of ammonium pyrrolidine dithiocarbamate (APDTC), an inhibitor of the nuclear translocation of the transcription factor κB (NF-κB), on the depolymerization of collagen, proteoglycans and sialoglycoproteins in extracellular matrix of soft and osseous tissues under modeled systemic inflammatory response (SIR). The latter was induced by intraperitoneal administration of lipopolysaccharide Salmonella typhi (pyrogenalum) in a dose of 0.4 μg/kg of weight 3 times during the first week, and once a week for the following 7 weeks. It has been shown the SIR simulation is accompanied by activation of the collagenolysis as well as depolymerization of proteoglycans and sialoglycoproteins in the tissues of the gum, periodontal ligament and alveolar process of the jaws as evidenced by a considerable increase in the concentration of free hydroxyproline, glycosaminoglycans and N-acetylneuraminic acid. The application of APDTC during SIR significantly reduces the depolymerization of collagen, proteoglycans and sialoglycoproteins in soft and bone periodontal tissues, and limits the degree of resorption of the jaw alveolar process. This allows us to conclude the use of this compound during SIR is an effective means to correct disruption the periodontal connective tissue in rats.